2011
DOI: 10.1007/s00894-011-1165-6
|View full text |Cite
|
Sign up to set email alerts
|

Signals of LOV1: a computer simulation study on the wildtype LOV1-domain of Chlamydomonas reinhardtii and its mutants

Abstract: Phototropins are photoreceptors regulating the blue-light response in plants and bacteria. They consist of two LOV (light oxygen voltage sensitive) domains each containing a non-covalently bound flavin-mononucleotide (FMN) chromophore, which are connected to a serine/threonine-kinase. Upon illumination, the LOV-domains undergo conformational changes, triggering a signal cascade in the organism through kinase activation. Here, we present results from molecular dynamics simulations in which we investigate the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 53 publications
(69 reference statements)
1
22
0
Order By: Relevance
“…From several experimental and theoretical investigations, 8,14,[51][52][53][54] it is well known that the three amino acids Gln513, Asn492, and Asn482 are essential in triggering the signaling pathway of the AsLOV2-Jα-as well as the PA-Rac1-system. We assume that these amino acids can carry out the following rate-dependent transformation processes, i.e., (1) side chain rotation, (2) H-bond formation, and (3) H-bond breakage, which are included in the list of events of the RB-KMC algorithm.…”
Section: Residue-based Kmcmentioning
confidence: 99%
“…From several experimental and theoretical investigations, 8,14,[51][52][53][54] it is well known that the three amino acids Gln513, Asn492, and Asn482 are essential in triggering the signaling pathway of the AsLOV2-Jα-as well as the PA-Rac1-system. We assume that these amino acids can carry out the following rate-dependent transformation processes, i.e., (1) side chain rotation, (2) H-bond formation, and (3) H-bond breakage, which are included in the list of events of the RB-KMC algorithm.…”
Section: Residue-based Kmcmentioning
confidence: 99%
“…Several recent MD studies on LOV domains have highlighted the role of rotamerization of a highly conserved glutamine residue (Q513 in AsPhot1-LOV2). In a series of simulations on LOV domains from various organisms, Baeurle and coworkers have highlighted the importance of a light-induced hydrogen bond between Q513 and N492 (using AsPhot1-LOV2 numbering) in AsPhot1-LOV2 44,46 and N. crassa Vivid 45 (but not in a LOV1 domain from C. reindardtii 47 . In the specific case of AsPhot1-LOV2, they concluded that disruption of the J α -LOV2 interface was triggered by stress due to the increased coupling of the H β and I β strands 44,46 , and subsequent breakage of Q497-D540 and Q479-E518 hydrogen bonds 44 .…”
Section: Introductionmentioning
confidence: 99%
“…To study the functional behavior of complex protein systems in nonequilibrium situations, we have recently introduced a novel noninvasive thermostating strategy, relying on the molecular dynamics (MD) algorithm,10–12 and demonstrated its usefulness to explore the early stages of the switching mechanism of the AsLOV2‐Jα photosensor at the molecular level. The so‐called noninvasive MD technique permits to sample the protein's configurations far from equilibrium and to follow its natural dynamics under solvent‐mediated thermostating control 10.…”
Section: Introductionmentioning
confidence: 99%